Supporting the educational attainment and progress of children in state care: A preliminary review of international evidence - Eavan Brady (Trinity College Dublin, The University of Dublin, Trinity Research in Social Sciences (TRiSS), 2017)
International research spanning a number of decades has highlighted the low educational attainment of children in care as compared to their peers in the majority population with many reasons reported as to why this is the case. Recent research in this area points to a number of key practice and policy responses that appear to support the educational progress of children in care. These practices include information sharing among key stakeholders, support from carers, teachers, and social workers, and recognition of the active role that children and young people play in their education.
Keywords: 330; Education; children in care; attainment